Validity and Reliability of the Indonesian Version of the Internalized Stigma Mental Illness Instrument: Substance Abuse in Adolescents - Suratmini, Dwi; Daulima, Novy Helena Catharina; Wardani, Ice Yulia (Fakultas Ilmu-ilmu Kesehatan, 2024)
The prevalence rate of drug abusers in adolescents in Indonesia is relatively high. There is no valid and reliable instrument in the Indonesian language to measure stigma in drug users in adolescents. Therefore, this study aims to measure the validity and reliability of the self-stigma questionnaire in adolescent drug users. This cross-sectional study involved 59 teenage drug users who, at the time of the study, were in good health and could read and write to answer the questionnaire. Data were collected between March and September 2020 using Internalized Stigma Mental Illness (ISMI): Substance Abuse questionnaire. Pearson’s correlation coefficient, r, was used to measure the cross-validity value of the correlation between item scores and total statement scores. Meanwhile, researchers used Cronbach’s Alpha to assess the internal consistency of the questionnaire. Pearson’s r values for 29 statements showed that 1 statement was invalid. After eliminating the invalid statements, 28 statements with valid results at rcount ≥ 0.256 and Corrected item-total correlation >0.3 with a confidence level of 95% (rcount 0.323-0.642) and reliable Cronbach Alpha > 0.700 (Cronbach Alpha If Items Deleted: 0.888-0.895) with a 95% confidence level were used in the instrument. The ISMI is a valid and reliable version of drug abuse that can be used as an assessment and evaluation tool for adolescent drug abusers in clinical, rehabilitation, research, and community settings.